The Valuation of Mangrove Forest Economy of Community Development Program of Badak LNG - Busori Sunaryo; Reta Yudistyana; Akhmad Taufiq Firaldy (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2018)
Mangrove forest is one of the resources that has important functions and roles in a single ecosystem. The utilization of mangrove forest also has a fairly high economic value. The existence of mangrove forest has several functions such as a media for mangrove crab cultivation, mangrove cultivation, diversification of mangrove products and mangrove tourism. Some of these benefits were introduced by CSR of Badak LNG program to society around the mangrove forest in Bontang City for the economic improvement of coastal communities by exploiting the existing mangrove potential. Thus, the aim of this study is to calculate the economic value of the utilization of mangrove forest. The research method used is quantitative method by using benefit cost analysis. In brief, the results showed that the utilization of mangrove resources conducted by the community or local community groups such as mangrove crab cultivation, mangrove seedling, mangrove dodol, mangrove syrup and mangrove tourism. The highest direct benefits of mangrove area came from mangrove seedlings (71%), mangrove dodol (9.76%), mangrove tourism (6.82%), mangrove crab (6.47%) and mangrove syrup (5.96 %). Meanwhile the value of choice for mangrove area is 30 Ha. From the calculation results, the benefit obtained of mangrove forest selection was Rp 6.087.150,00 per year. Based on the mentioned value, it indicated that the respondents were willing to pay for the existence of mangrove forest ranging from Rp 50.000,00 – Rp 750.000,00. The total existence value of mangrove forest was Rp 4.375.000,00 for 50 respondents and the total value of existence per year was Rp 52,500,000.00. The total benefit of mangrove forest was Rp 4,749,322,671,00 per year. As the result, the 87% indirect benefit is the largest contributor to the benefits of mangrove forests in South Bontang District. While the second largest contributor is a direct benefit of 12%.